Model Kolaborasi Petani Muda Dalam Ekosistem Wirausaha Pertanian (Sebuah Pengalaman pada Petani Muda Hortikultura di Jawa Barat) - Mukti, Gema Wibawa; Charina, Anne; Kusumo, Rani Andriani Budi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This paper aims to study collaboration between actors in the horticultural agricultural entrepreneurship ecosystem in West Java. The research method used in this paper is descriptive – qualitative analysis, with an analytical focus on quadruple helix collaboration between farming actors, government, universities and the agricultural industry, analyzing the knowledge transfer process carried out between the actors involved, to develop agricultural entrepreneurship. The research results explain that strengthening human resources and agricultural institutions is the main aspect in creating a competitive and productive agricultural entrepreneurship ecosystem. In its implementation, these programs have helped farmers in developing their farming businesses, both in terms of on-farm cultivation and farming management. However, on the other hand, program implementation in the field is still limited and not sustainable. To overcome this, synergistic collaboration is needed between the actors involved (government, universities, industry and farming actors). Information openness and intense communication can help the synergy process, so that the actors involved can mutually strengthen each other, making it easier to achieve activity outcomes, namely creating a conducive, productive and competitive agricultural entrepreneurship ecosystem.